Effects of Increased Feeding Rates on Oxidative Stress, Biochemical Indices and Growth of Juvenile Hybrid Grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) Under Mild-Hyperoxia Conditions - Zhiyi Wang; Yikai Zheng; Dengpan Dong; Xiefa Song; Meng Li (Fishes)
Evaluating the interaction between dissolved oxygen (DO) and feeding rates (FRs) in fish is crucial for the precise regulation of aquaculture water environments. This study established four treatment groups: the CK group (DO = 6 mg/L, FR = 2% of body weight), the HFR group (DO = 6 mg/L, FR = 3.5% of body weight), the HDO group (DO = 9 mg/L, FR = 2% of body weight), and the MIX group (DO = 6 mg/L, FR = 3.5% of body weight). The combined effects of dissolved oxygen and feeding levels on oxidative stress, biochemical indicators, and growth in the hybrid grouper were evaluated. The results showed that mild hyperoxia significantly upregulates the expression of antioxidant enzyme genes (cat, cu/zn-sod, and gpx1a). Under conditions of mild hyperoxia, an increased feed rate can significantly downregulate the expression of cat and gpx1a. Additionally, serum levels of carnosine and cndp1 in muscle tissue are significantly elevated. Furthermore, a high FR mitigates the downregulation of glucose, triglycerides, and alanine aminotransferase (ALT) induced by mild hyperoxia while alleviating the upregulation of aspartate aminotransferase (AST). The combined effects of mild hyperoxia and high FR significantly enhance final body weight and specific growth rate (SGR), with notable interactions observed. Mild hyperoxia reduces serum levels of bile acids and glycocholic acid under high feeding conditions while significantly downregulating the expression of ghrb in both liver and brain tissues. In summary, high FRs alleviate oxidative stress and energy substrate deficiency in juvenile hybrid grouper under mild-hyperoxia environments. Moreover, the synergistic effect between mild hyperoxia and high FR promotes growth by improving bile acid enterohepatic circulation. This study provides a reference for the regulation of DO and feeding in modern industrial intensive mariculture.